LELANG TERHADAP OBJEK JAMINAN FIDUSIA YANG DIRAMPAS OLEH NEGARA BERDASARKAN PUTUSAN PENGADILAN NEGERI DI KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG PADANG - ferdian, ferdian (Soumatera Law Review, 2019)
Deprivation of evidence must be carried out in accordance with the provisions of the law, principles, and principles justified by law, as a form of a rule of law that has bodies or executors of legal regulations. At this writing the object of the booty which is then auctioned is a Collateral Object tied to Fiduciary. The research method uses a sociological juridical approach. The results of the study explained that the legal nature of the booty that could be seized by the state based on a court decision that had permanent legal force must belong to the defendant and the object seized must have a direct relationship with the criminal act committed. The auction of objects of fiduciary confiscation by the State based on the decision of the Padang District Court at the State Wealth Service Office and Padang Auction, Padang District Attorney as executor of the verdict and KPKNL decision as the Institution appointed as the auctioneer has carried out the auction process in accordance with the procedure and the applicable rules, the implementation of the booty auction carried out has a mechanism and rules regarding its implementation. Legal certainty towards the auction buyers of the object of fiduciary collateral seized for the State based on the decision of the Padang District Court in fact became a guarantee in the Leasing company PT. The auction buyer Adira Dinamika Multi Finance, is still not felt by auction buyers, it is proven that there are various problems that arise after auction buyers are declared as auction winners, in terms of handling ownership documents up to security in utilizing vehicles purchased through the booty auction process.